Transcriptional analysis of oxidative and nitrosative stress on oral opportunistic Candida albicans: Oxidative and nitrosative stress on oral opportunistic Candida albicans - Ali Mohammed, Rezhin; Abdulmuhsin Mohammad, Karzan (Cellular and Molecular Biology, 2024)
The yeast Candida albicans is one of the most aggressive opportunistic pathogens in immunocompromised patients. The ability of the yeast to withstand stresses and radicals is of great concern. In the present study, four isolates of C. albicans were taken from patients with oral candidiasis and grown on RPMI for 24 hours at 37°C. Then, they were exposed to various concentrations of oxidative (H2O2) and nitrosative (HNO3) stress for two hours, and gene expression rates were measured through RT-PCR. After initial biofilm formation steps and growth validation, RNA extracted from the yeast and gene expression status were evaluated. Upon treatment with H2O2, the gene expression profile for ALS1, MLH1, and EXO1 showed approximately a fold increase in expression. While within HNO3 the yeast gene expression exhibited a dramatic increase in ALS1 up to 217 folds, while others such as MLH1, HWP1, and ERG11 showed a one-fold increase in the expression rate. The findings of this research indicate a considerable expression activity within the biofilm of Candida albicans, increased rate of DNA mismatch repair and break fixation may indicate the ability of the yeast to tolerate high concentrations of free radicals. It paves the way toward understanding the pathogenicity of the yeast and its survival capability inside macrophages. The study also revealed that the biofilm strategy of the yeast is more active within these stresses.